Plummer–Vinson syndrome in celiac disease - Sharma, Zubin Pradeep; Sharma, Divya; Sharma, Ravindra; Yadav, Santosh Kumar (Indian Journal of Case Reports, 2020)
The association of Plummer–Vinson syndrome (PVS) and celiac disease is not widely reported. Both entities have associated iron deficiency anemia. The following case report signifies that the diagnosis of celiac enteropathy must be kept in mind in every iron deficiency case that we encounter, principally when associated with Plummer–Vinson. We report two cases which emphasize the need for definitive screening for celiac disease in outdoor patients with PVS.